2012
DOI: 10.1007/s13311-011-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Leucine Zipper (GILZ) Over-Expression in T Lymphocytes Inhibits Inflammation and Tissue Damage in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a traumatic event that causes a secondary and extended inflammation characterized by infiltration of immune cells, including T lymphocytes, release of pro-inflammatory mediators in the lesion site, and tissue degeneration. Current therapeutic approaches for SCI are limited to glucocorticoids (GC) due to their potent antiinflammatory activity. GC efficacy resides, in part, in the capability to inhibit NF-κB, T lymphocyte activation, and the consequent cytokine production. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 48 publications
0
47
1
1
Order By: Relevance
“…Indeed, in more complex models of inflammation where TAT-GILZ was used it was an effective strategy to control inflammation. For instance, TAT-GILZ administration promoted a protective effect in a model of inflammatory bowel disease (9) and spinal cord injury (12). Moreover, recent studies showed that GILZ overexpression inhibits endothelial cell adhesion function (42) and protects against endotoxemia (43) and arthritis (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in more complex models of inflammation where TAT-GILZ was used it was an effective strategy to control inflammation. For instance, TAT-GILZ administration promoted a protective effect in a model of inflammatory bowel disease (9) and spinal cord injury (12). Moreover, recent studies showed that GILZ overexpression inhibits endothelial cell adhesion function (42) and protects against endotoxemia (43) and arthritis (13).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are thought to be important for their ability to attenuate inflammation (8). GILZ appears to have a physiological role in the regulation of inflammatory mechanisms; however, there are few reports that explore its role in inflammatory disease (9)(10)(11)(12)(13).…”
Section: R Esolution Of Inflammation Is An Active and Continuousmentioning
confidence: 99%
“…Therefore, the rescue of sepsis through propofol use in the clinic still had great theoretical risk. Many other drugs can also be used for anti-inflammation effects; thus, the clinical application of propofol still lacks powerful physiological and pharmacological support (Esposito et al, 2012). Considering the question of cardiovascular safety, etomidate has received more attention for its reduced impact on cardiovascular function and stable hemodynamics (He et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord sections from control-and RCE-treated animals were stained as a set to compare identically processed tissue. The slices were observed under a microscope by blinded investigators who scored the samples on a scale of 0-4 for oedema, where 0 indicates no or minor levels of neutrophil infiltration and haemorrhage; 1 indicates modest or limited, 2 indicates intermediate, 3 indicates widespread or prominent, and 4 indicates widespread and highly prominent levels [1,17].…”
Section: Haematoxylin-eosin (Hande) Stainingmentioning
confidence: 99%